Effect Job Pressure on Employee Performance in Indonesia - Nurul Komari (Enrichment : Journal of Management, 2023)
Work pressure has taken various forms in every workplace and is a worldwide phenomenon. Employees in general are currently working longer hours due to increased responsibilities and workloads along with increased work performance demanded by companies to be competitive. This study examines the effect of work pressure on job satisfaction and employee performance. Respondents in this study were 100 insurance company employees. This study uses primary and secondary data. Primary data were obtained through questionnaires and in-depth interviews. This study found that work pressure has a negative and insignificant effect on employee job satisfaction, job satisfaction has a positive and significant effect on employee performance, and work pressure has a negative and insignificant effect on employee performance. The effect of work pressure on employee performance through job satisfaction is not significant.